Relationship marketing in football clubs - Myskiw, Mauro (2009)
This essay reflects on marketing in the management of football clubs by examining the fundamentals and assumptions of relationship marketing. It is divided in two parts: in the first, we will present the fundamentals of relationship marketing, focussing on the notions of relational exchanges, trust and commitment; then in the second part, we will attempt to systematize an approach to the management of clubs, recognizing marketing as a centre of competencies present both within and outside the organization, consisting of strategic skills.